Hierarchization of Physicochemical Factors during Simultaneous Removal of Lead and Copper from the Marrakech Municipal Discharge Soils - Abdelaaziz Aityoub; Abdessalem Abouelfida; Abdelaziz Benyaich; Mohamed Elmeray; Rachid Idouhli; Yassine Koumya; Mohyeddine Khadiri (Journal of Chemistry, 2020)
Heavy metals became a great concern for scientists due to their harmful action on the environment and human life. EDTA and NTA chelation capacity were used to assess soil decontamination. The effect of pH, ligand, soil solution contact time with agitation, soil solution ratio, and particle size were investigated, in order to prioritize them, using the design of experiment methodology (Doe): pH was the most influential factor while the ratio mass of the soil by the volume of the solution and particle size were of equal importance. EDTA was more effective as a chelator than NTA in removing metals from the soil. The contact time was not a significant factor; a contact time of 10 minutes was sufficient to extract the two metals studied. An extraction efficiency of 45% was achieved for Pb and 85% for Cu without optimization process.